2015
DOI: 10.1016/j.apmr.2014.07.426
|View full text |Cite
|
Sign up to set email alerts
|

Focal Hand Dystonia: Individualized Intervention With Repeated Application of Repetitive Transcranial Magnetic Stimulation

Abstract: Objective Examine for individual factors that may predict response to inhibitory repetitive transcranial magnetic stimulation (rTMS) in focal hand dystonia (FHD); present method for determining the optimal stimulation to increase inhibition in a given patient; and examine individual responses to prolonged intervention. Design A single-subject design to determine optimal parameters to increase inhibition for a given subject and to employ the selected parameters 1/wk for 6 weeks, with 1 wk follow up, to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Indeed, in a pilot study of a 6 week session of inhibitory low frequency rTMS administered over the contralateral dorsal PMC of two focal hand dystonia patients, only the patient with reduced CSP and SICI, which reflects a loss of cortical inhibition, had clinical benefit from rTMS while the other patient without CSP and SICI reduction did not improve (Kimberley et al, 2015a). …”
Section: Therapeutic Procedures In Dystoniamentioning
confidence: 99%
“…Indeed, in a pilot study of a 6 week session of inhibitory low frequency rTMS administered over the contralateral dorsal PMC of two focal hand dystonia patients, only the patient with reduced CSP and SICI, which reflects a loss of cortical inhibition, had clinical benefit from rTMS while the other patient without CSP and SICI reduction did not improve (Kimberley et al, 2015a). …”
Section: Therapeutic Procedures In Dystoniamentioning
confidence: 99%
“…For instance, it has been reported that only patients with a modulation of cortical inhibition do respond to rTMS treatment (Kimberley et al, 2015). …”
Section: Therapeutic Approaches In Dystonia: State Of Artmentioning
confidence: 99%
“…11 However, their value in predicting the best type of rehabilitation intervention is not well understood. In addition, work in this area has focused on adults with stroke; a rich opportunity exists to broaden these questions to include other types of neurological disorders 68 as well as ask questions across the life span. Children appear to respond differently since their motor skills and repertoire are still being established, and, therefore, treatment plasticity and reorganization are different to adults with well-defined motor maps and pathways.…”
Section: Personalizedmentioning
confidence: 99%